The runaway [large type] - Petrie, Nicholas (Petrie, Nicholas. Peter Ash novel, 2022)
"When Peter Ash rescues a stranded woman, he finds she's in far deeper trouble than he could ever imagine in the powerful new thriller in this bestselling and award-winning series. "Explosive and engaging! Fasten your seat belt, this is going to be a wild ride."--Lisa Gardner War veteran Peter Ash is driving through northern Nebraska when he encounters a young pregnant woman alone on a gravel road, her car dead. Peter offers her a lift, but what begins as an act of kindness soon turns into a deadly cat-and-mouse chase across the lonely highways with the woman's vicious ex-cop husband hot on their trail. The pregnant woman has seen something she was never meant to see . . . but protecting her might prove to be more than Peter can handle. In order to save the woman and himself, Peter must use everything he has learned during his time as a Marine, including his knowledge of human nature, in order to escape a ruthless killer with instincts and skills that match--and perhaps exceed--Peter's own"--